2014
DOI: 10.1261/rna.042747.113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular crowders and cosolutes promote folding cooperativity of RNA under physiological ionic conditions

Abstract: Folding mechanisms of functional RNAs under idealized in vitro conditions of dilute solution and high ionic strength have been well studied. Comparatively little is known, however, about mechanisms for folding of RNA in vivo where Mg 2+ ion concentrations are low, K + concentrations are modest, and concentrations of macromolecular crowders and low-molecular-weight cosolutes are high. Herein, we apply a combination of biophysical and structure mapping techniques to tRNA to elucidate thermodynamic and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 77 publications
(87 reference statements)
4
75
0
Order By: Relevance
“…Several recent studies focused on mimicking aspects of the in vivo environment in vitro ; conditions referred to herein as ‘ in vivo-like ’ conditions (Figure 3). Effects of such conditions as cellular concentrations of monovalent and divalent ions and molecular crowding agents on the folding of RNAs have been a theme in a number of recent studies (Desai et al, 2014; Dupuis et al, 2014; Nakano et al, 2015; Paudel & Rueda, 2014; Strulson et al, 2014; Tyrrell et al, 2015). Experiments under these in vivo-like conditions have the potential to bridge our understanding of observations made in vitro and in vivo .…”
Section: Bridging the Gap Between In Vitro And In Vivo Rna Foldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies focused on mimicking aspects of the in vivo environment in vitro ; conditions referred to herein as ‘ in vivo-like ’ conditions (Figure 3). Effects of such conditions as cellular concentrations of monovalent and divalent ions and molecular crowding agents on the folding of RNAs have been a theme in a number of recent studies (Desai et al, 2014; Dupuis et al, 2014; Nakano et al, 2015; Paudel & Rueda, 2014; Strulson et al, 2014; Tyrrell et al, 2015). Experiments under these in vivo-like conditions have the potential to bridge our understanding of observations made in vitro and in vivo .…”
Section: Bridging the Gap Between In Vitro And In Vivo Rna Foldingmentioning
confidence: 99%
“…Various methods, including UV melts, SAXS, kinetic techniques, and smFRET, have been used to study RNA under these in vivo-like conditions. Several studies have shown that synthetic crowding agents affect the thermodynamics and function of several RNAs (Dupuis et al, 2014; Kilburn et al, 2013; Kilburn et al, 2010; Lambert et al, 2010; Strulson et al, 2014). Findings of these studies are that RNAs fold cooperatively, structure becomes compact, and ribozymes cleave faster under in vivo-like conditions (Kilburn et al, 2013; Nakano et al, 2009; Strulson et al, 2014; Strulson et al, 2013).…”
Section: Bridging the Gap Between In Vitro And In Vivo Rna Foldingmentioning
confidence: 99%
“…-the effects of crowding on the structure in vivo of chromatin which contains DNA in conformations other than the classical B-form double helix, such as the DNA in telomeres whose conformation in vitro is strongly influenced by crowding [80]; -the consequences of crowding for the structures of RNAs and ribonucleoproteins in vivo; the folding and stability of RNA in vitro are enhanced significantly by crowding [81][82][83]; -loops in chromatin fibers in vivo are usually thought to be stabilized by proteins such as cohesin (for example [84]). Reports that nucleosomes which contain identical DNA sequences can self-associate preferentially [85] raise the possibility that similar interactions could contribute to the formation and stabilization of loops [86].…”
Section: Future Challenges and Directionsmentioning
confidence: 99%
“…Coupled tertiary interactions that form early in the folding process have been observed in the group I self-splicing intron, which promote proper RNA folding by suppressing nonnative structures [11]. The network of peripheral tertiary elements might be more important within the cellular environment as RNA tertiary interactions are strengthened relative to secondary interactions within macromolecular crowders and cosolutes [12]. The highly coupled nature of tertiary structure in RNA also likely makes it poorly suited for modulation of activity such as regulatory tuning.…”
Section: Discussionmentioning
confidence: 99%
“…The coupled and cooperative tertiary interactions assist the RNA in traversing a rugged folding landscape. Further, studies have recently started to focus on RNA structure and folding under conditions mimicking physiological conditions [1214] or co-transcriptional constraints [1517]. Transcriptional riboswitches are an ideal model system for studying RNA folding under co-transcriptional constraints because a regulatory decision via transcriptional termination or read-through must be made at the time the RNA polymerase reaches the poly-uridine tract of the intrinsic (rho-independent) terminator [18].…”
Section: Introductionmentioning
confidence: 99%